Big Sister, Big Brother: A Mixed Methods Study on Older Siblings' Role in Infant and Young Child Feeding and Care in Rural Tanzania (P10-020-19). (13th June 2019) - Boncyk, Morgan; Ambikapathi, Ramya; Mosha, Dominic; Matangi, Evidence; Galvin, Lauren; Jeong, Joshua; Sultan, Reina; Kumalija, Elfrida; Kajuna, Deus; Kieffer, Mary Pat; Sando, Mary Mwanyika; Yousafzai, Aisha; et al.
Abstract: Objectives: Nutrition interventions to improve infant and young child feeding (IYCF) and care in developing countries usually target mothers, while critical roles of other family members, particularly older siblings, are not well known. As part of the Engaging Fathers for Effective Child Nutrition and Development in Tanzania (EFFECTS) cluster-randomized trial (ClinicalTrials.gov: NCT03759821), we examined the roles of older children and adolescents in IYCF and care in rural Tanzania to develop and administer informed quantitative questionnaires on IYCF and care by older siblings. Methods: Twelve mothers, 12 fathers, 4 grandmothers, and 4 older siblings (7–17 years of age) were purposively sampled for qualitative interviews conducted July-August 2018. Open-ended questions explored older siblings' roles in IYCF and care, managing time for child care, and responsiveness to young children's hunger cues. Inductive and deductive approaches were used to identify themes from transcribed interviews. Findings supported development of two questionnaires on older children's roles in IYCF and care (14 questions each) that were administered to mothers and siblings in the EFFECTS baseline. Results: Qualitative data indicate older siblings (male and female) are involved in food preparation (e.g., starchy staples), daily feeding, hygiene (e.g., washing baby after toileting) and care when the mother is unavailable due to other household activities. The EFFECTS study enrolled 960 households across 80 villages in Mara, Tanzania, and 53% of households identified at least one sibling who cares for an index child aged 0–18 months. Baseline data collection is ongoing and indicates prevalence and types of child care (e.g., feeding, playing, hygiene, responding to crying) provided by older siblings. Conclusions: To our knowledge, this is the first mixed methods study developing instruments to investigate the role of older siblings in providing IYCF and care in a rural, developing country setting. As parents seek to meet household and livelihood needs, older siblings are often engaged in child feeding and care. Nutrition interventions should consider roles of all family members, including older children, in child feeding and care. Further research is needed to evaluate the effect of family-based interventions. Funding Sources: Eleanor Crook Foundation and Conrad N. Hilton Foundation.